Rethinking the role of research - Myers, Mark B.
Mark B. Myers and Richard S. Rosenbloom explain how repositioning a firm's research function as part of its "engine of innovation" is necessary for meeting today's competitive challenges.
Leadership in marketplace innovation requires mastering 'radical incrementalism.'
In today's competitive environment, large, mature, technology-based enterprises must restore the high levels of innovativeness that made them great in the first place. Repositioning the research function as part of the firm's "engine of innovation" should be an important priority. Central to that task in many industries is the capacity to identify, develop and exploit wholly new technologies that will give rise to new classes of customers, channels and uses. At the confluence of emergent markets and technologies, innovative success will require that research acquire a new set of organizational capabilities. Given the inherent unpredictability of the details and timing of future markets, radical incrementalism-the testing of radically new concepts in a series of practical market engagements based on a larger research vision and technology strategy-provides a key capability to explore the uncertain dynamics of demand.
Keywords: Research